2014
DOI: 10.14455/isec.res.2014.79
|View full text |Cite
|
Sign up to set email alerts
|

Building Information Modeling (Bim) Roles in the Malaysian Construction Industry

Abstract: Building Information Modeling (BIM) represents a new paradigm in the Malaysian architecture, engineering, and construction (AEC) industry. BIM technology provides virtual models (including 3-D models) to generate a building’s entire lifecycle. The model can also be used for analyzing design clashes, project scheduling, cost estimation, and facility management. The use of BIM in construction projects can reduce time to develop a project, reduce construction cost, and increase project quality. This paper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
141
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 84 publications
(143 citation statements)
references
References 2 publications
1
141
0
1
Order By: Relevance
“…Since BIM is the core of this bi-directional coordination, its role is to digitize and control the overall process of the construction life cycle. However, for this to be realized, the construction industry needs to accommodate their activities with BIM functionalities, as BIM tools have the potential to be used for managing different activities [67]. BIM functionalities include six components [68]:…”
Section: Concept Matrix Inmentioning
confidence: 99%
“…Since BIM is the core of this bi-directional coordination, its role is to digitize and control the overall process of the construction life cycle. However, for this to be realized, the construction industry needs to accommodate their activities with BIM functionalities, as BIM tools have the potential to be used for managing different activities [67]. BIM functionalities include six components [68]:…”
Section: Concept Matrix Inmentioning
confidence: 99%
“…Apart from Government should provide BIM guideline. 6 A strategic approach model is required to assist construction players to implement BIM in construction projects. 7…”
Section: Conclusion and Further Workmentioning
confidence: 99%
“…The committee also prepared a BIM standard manual documentation as a guideline for construction players reference in managing Malaysian government projects [9][10][11]. Moreover, there were several BIM pilot projects, which have been monitored by PWD such as NCI project, Type 5 Clinic (KK5) Sri Jaya Maran, Pahang and Administration Complex of Suruhanjaya Pencegah Rasuah Malaysia (SPRM) Shah Alam, Selangor [6,9,12]. The purpose of running BIM pilot projects is to test the capability of the PWD committee to manage projects using BIM [12].…”
mentioning
confidence: 99%
“…Recent studies show that advanced technologies played an essential role in improving the traditional practice. The graphical approach for evaluating the impacts of change orders such as Building Information Modeling (BIM) is still limited even though a number of previous studies confirmed that BIM can assist in tracking design changes across multi-disciplinary [10], contributing to successful construction projects [11].…”
Section: Introductionmentioning
confidence: 99%